2001
DOI: 10.1002/1522-2683(200108)22:13<2709::aid-elps2709>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoretic bioanalysis of therapeutically active peptides with UV and mass spectrometric detection after on-capillary preconcentration

Abstract: An earlier developed capillary electrophoresis (CE) system with an on-capillary adsorptive phase is investigated for its suitability to quantitate low concentrations of angiotensin II and gonadorelin in plasma. An off-line solid-phase extraction is used for sample preparation. The on-line preconcentration CE system allows multiple capillary volumes of sample solution to be injected, increasing the concentration sensitivity of CE with 3-4 orders of magnitude. Furthermore, possible influence of matrix salts can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Waterwal et al [80][81][82] reported some studies regarding the use of mPC-CE for the preconcentration and separation of angiotensin II and gonadorelin. In a preliminary study they compared different in-line SPE-CE designs for preconcentrating the two peptides.…”
Section: Disksmentioning
confidence: 99%
See 1 more Smart Citation
“…Waterwal et al [80][81][82] reported some studies regarding the use of mPC-CE for the preconcentration and separation of angiotensin II and gonadorelin. In a preliminary study they compared different in-line SPE-CE designs for preconcentrating the two peptides.…”
Section: Disksmentioning
confidence: 99%
“…After coupling the same mPC-CE system to a mass spectrometer using a sheathless interface, the sensitivity for a standard solution of the same compounds improved considerably the picomolecular range in the selected ion monitoring mode (SIM) [81]. Finally, the authors used this approach (mPC-CE-MS) to determine the two peptides in spiked plasma samples in the low nanomolar concentration level [82] but in this case for avoiding contamination of the membrane and of the capillary wall a pre-treatment step based of an off-line procedure and a rinsing of the capillary with SDS were necessary.…”
Section: Disksmentioning
confidence: 99%
“…A means to close the CE electrical circuit for analyte separation while simultaneously providing an electrical potential to the spray tip is necessary. The common interfaces can be divided into three categories: sheath-flow 16,[18][19][20]24,27,32,37,38,40,43,47,50,[53][54][55][56]60,66 and sheathless 15,17,25,26,[28][29][30]34,36,44,45,48,49,61 and liquid-junction interfaces. [92][93][94] In the sheath-flow design, a coaxial sheath liquid, usually a hydroorganic mixture, mixes with the capillary eluent at the outlet end of the capillary.…”
Section: ·1 Esi-msmentioning
confidence: 99%
“…They applied this later to quantitate low concentrations of gonadorelin and angiotensin II in a plasma. 30 Janini et al 49 assembled a miniaturized, membrane-based solid-phase extractor (mSPE) using a C18-impregnated extraction disk (Fig. 4).…”
Section: Sample-enrichment Techniquesmentioning
confidence: 99%
“…We have chosen on-line coupling of in-capillary µSPE for sample purification and concentration, CE for separation and nESI-MS for detection. On-line SPE-CE has been reported (for analytes other than HAs) using different SPE matrices, such as packed particle beds [20,21,22,23], C 18 -impregnated membranes [24] and polymer membranes [25,26]. The focus of this work was on the construction of the µSPE-CE-nESI capillary and its use in rapid analyses of small amounts of HAs.…”
Section: Introductionmentioning
confidence: 99%